2021
DOI: 10.1097/jnn.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Association Between Stroke Knowledge and Health Behavior Before the Onset of Stroke Among Chinese Hypertensive Patients

Abstract: BACKGROUND: Previous research has shown that men and women have different levels of stroke knowledge and differing health behaviors, which are important factors affecting blood pressure, as hypertension is a key risk factor for stroke occurrence. There has been little research on the effects of sex on the association between these 2 variables before the onset of stroke among Chinese hypertensive patients. METHODS: A cross-sectional study and a convenience sampling method were used. 272 male and 118 female hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In the complex process of behaviors change, multiple factors were associated with health behaviors. As reported previously (22), we found that female patients displayed better health behaviors than male patients. The "traditional masculinity" that requires men to be more independent and resilient may be an important reason for this phenomenon (23).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the complex process of behaviors change, multiple factors were associated with health behaviors. As reported previously (22), we found that female patients displayed better health behaviors than male patients. The "traditional masculinity" that requires men to be more independent and resilient may be an important reason for this phenomenon (23).…”
Section: Discussionsupporting
confidence: 89%
“…The "traditional masculinity" that requires men to be more independent and resilient may be an important reason for this phenomenon (23). Additionally, the male-female differences in the division of labor and dietary habits also affected patients' health behaviors (22). Thus, health education content needs to be designed for stroke patients of different genders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that gender and education level are important factors affecting health behaviour of stroke patients (Wan et al, 2014; Yuan et al, 2015). Li et al (2021) investigated gender differences in health behaviour among hypertensive Chinese patients and found that female patients showed better health behaviours than male counterparts for nutrition and smoking and alcohol abstinence/reduction. Another cross‐sectional study revealed greater adherence of female stroke patients to fruit and vegetable consumption than males (Lennon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This allowed ample time to assess patients' knowledge about HTN, review and adjust medications, guide and support necessary lifestyle changes, set goals, examine and address barriers to adherence, and answer patient questions. Advanced practice providers are trained to individualize care to improve health behavior (Li et al, 2021). Much of the patient education was based on previous data showing that education provided by clinicians is essential to achieving targeted BP (Carter, 2018).…”
Section: Methodsmentioning
confidence: 99%